Synthesis of Bis-heterocyclic phenyl containing -4 – oxo – 1,3 – thiazolidine, 2,3 – dihydrothiazole, 1, 2,4 – triazolo [3, 4b ] – 1,3,4 – thiadiazine and pyrazol derivatives - Al - Daeif, Yasmeen A (Al-Nahrain Journal of Science, 2018)
This research describes the synthesis of some new different substituted bicyclic phenyl derivatives. To obtain the target compounds, the reaction steps shown in scheme (I) and (II) were of a feasible strategy. The synthon terphthalic acid hydrazide [2] which was prepared from methyl terphthalate [1] with hydrazine hydrate, was used for the preparation of six types of new heterocyclic derivatives. Acid hydrazide [2] reacts with carbon disulfide in the presence of potassium hydroxide and p–hydroxy benzaldehyde to give the corresponding potassium carbodithioate salt [3] and shiff’s base [5] derivatives respectively. Treatment of the latter salt with p- bromophenacyl bromide afforded thiazolidine -2- thione[4], cyclization of shiff’s base [5] using mercapto acetic acid resulted in the formation of -4- oxo-1,3 - thiazolidne [6]. 1,2,4 – triazolo [3, 4b] - 1,3,4 – thiadiazine [9] was synthesized from basic cyclization of the intermediate product [8] which was obtained from the reaction between 2 – mercapto – 1,3,4 – oxadiazole [7] and p-bromo phenacyl bromide. Furthermore, the hydrazino – 1,3,4 – oxadiazole [10], which was obtained from the reaction between of compound [7] with hydrazine hydrate, was then reacted with CS2 / pyridine and acetyl aceton to give the corresponding 1,3,4 – triazolo [5,1b] oxadiazole [11] and pyrazole [12] derivatives respectively, scheme (II). All synthesized compounds structures were characterized by measurements some of its physical proprieties and some specific reactions and spectral methods FTIR, 1H NMR for compound [6] and [8].